TI_GERICHTE 11.2022.19 vom 27. November 2023 , Diritto d'abitazione: suddivisione delle spese tra proprietario e usuario - TI Tribunale d'appello (2023)
Diritto d'abitazione: suddivisione delle spese tra proprietario e usuario